A Novel Stable Isotope Approach Demonstrates Surprising Degree of Age-Related Decline in Skeletal Muscle Collagen Proteostasis. Issue 4 (10th May 2021) - Abbott, Claire B; Lawrence, Marcus M; Kobak, Kamil A; Lopes, Erika Barboza Prado; Peelor, Frederick F; Donald, Elizabeth J; Van Remmen, Holly; Griffin, Timothy M; Miller, Benjamin F
Abstract: Age-related deterioration in turnover of collagen proteins accelerates extracellular matrix fibrosis and hinders adaptation to external stimuli. This project sought to understand factors that increase skeletal muscle fibrosis with age by studying what we term the dynamic protein pool. We hypothesized that the dynamic protein pool size of muscle collagen decreases with age, thus indicating a decrease in proteostatic maintenance (ie, ability to maintain proteostasis), and that failure to account for these changes impacts the interpretation of tracer-measured synthesis rates. We used deuterium oxide (D2 O) labeling for up to 60 days in adult (6 months) and old (23 months) mice. The dynamic protein pool in adult skeletal muscle was 65% in tibialis anterior (TA), but only 28% in gastrocnemius (Gastroc). In aged muscle, the dynamic protein pool was further decreased to only 35% and 14% for TA and Gastroc, respectively. We showed that this loss in dynamic pool size was associated with increases in markers of fibrosis and decreased proteostatic maintenance. We demonstrate that aged muscle has higher rates of collagen protein synthesis and lower rates of collagen protein breakdown, which causes collagen accumulation. We further demonstrated that the normal assumption of complete protein renewal and the standard practice of taking a single sample with isotope labeling have profound impacts on interpretation of the genesis of fibrosis. Strategies to maintain muscle function with aging should focus on the dynamic protein pool with attention to methodological strategies to assess those changes. Graphical Abstract: